2011
DOI: 10.2478/v10175-011-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive synthesis of a wavelet transform using fast neural network

Abstract: Abstract. This paper introduces a new method for an adaptive synthesis of a wavelet transform using a fast neural network with a topology based on the lattice structure. The lattice structure and the orthogonal lattice structure are presented and their properties are discussed. A novel method for unsupervised training of the neural network is introduced. The proposed approach is tested by synthesizing new wavelets with an expected energy distribution between low-and high-pass filters. Energy compaction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…They are computationally efficient and powerful tools of digital signal processing which find wide application in, e.g., compression, filtering, and encryption of data [24][25][26][27][28][29][30][31][32]. FPOTs usually adopt the computational structures of known transforms with determined basis vectors.…”
Section: Fast Parametric Orthogonal Transformsmentioning
confidence: 99%
“…They are computationally efficient and powerful tools of digital signal processing which find wide application in, e.g., compression, filtering, and encryption of data [24][25][26][27][28][29][30][31][32]. FPOTs usually adopt the computational structures of known transforms with determined basis vectors.…”
Section: Fast Parametric Orthogonal Transformsmentioning
confidence: 99%
“…Adding the watermark to the most prominent coefficients of phase of the DFT was proposed by Ruanaidh in [9]. The watermarking algorithm must take into consideration that the image to be real imposes the condition (11). So when watermarking, changes of phase must preserve negative symmetry:…”
Section: Dft Algorithm In the Same Article [2]mentioning
confidence: 99%
“…It has been shown that DWT performed best in all experiments. Further research should include adaptive DWT-based algorithms [11], complex domains, such as DWT-SVD and adaptive transforms, with particular emphasis on DWT adaptive transforms.…”
Section: On Domain Selection For Additive Blind Image Watermarkingmentioning
confidence: 99%
“…Moreover, special types of neural networks are used for adaptive synthesis of the wavelet transform [8], image segmentations [9] and systems identification and diagnosis [10,11], which proves that ANNs can be used in many technical areas. Based on this fact, for the prediction of corrections, the method based on artificial neural networks is examined in detail in this paper.…”
Section: Introductionmentioning
confidence: 99%